Learners’ self efficacy and academic performance of distance learning students in selected Kenyan public universities - Wambua, Rebecca; Gakuu, Christopher; Kidombo, Harriet; Ndege, Speranza (IISTE, 2018)
Academic performance of distance learning students has been of concern to researchers. Several researches done since 1920s in developed countries have revealed that there is no significant difference in performance between distance learning students and conventional students. In Kenya, however, the result findings have been inconsistent. The objective of this study was to establish the moderating influence of learners’ self efficacy on the relationship between institutional factors and academic performance of distance learning students. The study is based on pragmatism due to its focus on objectivity and use of scientific methods. Mixed methods of research were used. The target population consisted of 847 Bachelor of Education (Arts) distance learning students, 149 lecturers teaching distance learning students and 2 administrators in charge of distance learning programmes. The research instruments consisted of questionnaires, interview guides, document analysis and the instrument for measuring academic performance. The findings indicated that the moderating influence of learners’ self efficacy on the relationship between institutional factors and academic performance was statistically significant.
Keywords: Distance learning students; learners’ self efficacy; academic performance